Leading from the middle: vice-principals in Singapore as boundary spanners. Issue 2 (25th September 2020) - Ho, Jeanne; Kang, Trivina; Shaari, Imran
Abstract : Purpose: The purpose of this paper is to examine leading from the middle, which is consistent with calls to distribute leadership, while expanding the direction of influence, from the normal top-down to include a bottom-up or lateral direction. The paper proposes that the position of the vice-principal enables the role incumbent to lead from the middle as a boundary spanner. The research question was what leadership from the middle looks like for vice-principals. Design/methodology/approach: The study consisted of interviews of 28 vice-principals and 10 principals. A mixed case and theme-oriented strategy was adapted, with member checking with each vice-principal. Findings: The findings indicate that in leading from the middle, vice-principals play boundary spanning roles of connecting, translating and brokering: (1) connecting between organisational levels, (2) translating between vision/direction and actualisation, (3) connecting between middle managers and (4) brokering and translating between the ministry and the school. Originality/value: Leading from the middle is a nascent concept which is worth exploring, given the complexity of educational systems with multiple ecological levels, and the need for leadership to create coherence between the levels.